Construções possíveis: o convívio em um projeto público de acolhimento familiar - Dias, Walkyria Acquesta (2009)
This study discusses the practice of a pilot project of family foster care in the light of concepts considered relevant to the subject: ethical-political suffering, bond and attachment, family, resilience and social policy. It also refers to studies on the specific theme of foster family works in Brazil in recent years. From the monitoring of a child and a teenager during a process of formal family fostering, it tries to understand the contribution of this proceeding as they return to their birth families. It especially shows how the experience of living together was set up considering the relationship between the individuals as well as how the learning and other gains, both for the individual and the family, were developed during the process. It discusses the experience of living together, both within the birth and the foster family, as well as between the families themselves, highlighting the subject of affective ties in contexts of social vulnerability. In this regard, it is highlighted that the previously established relationship with the birth family is not affected by the new ties built with the foster family, the latter, moreover, providing itself as another reference of respect and affection for both the individual and their family. Being a pilot project designed for a public policy, it deals with structural issues, relating them to ideas concerning the experience of living in a family. Accordingly, the study addresses cross-sectoral issues when implementing the measure, demanding a democratic management and clarity of roles, so that the actions of various institutions involved ensure the aims of the proposal, without overlapping themselves or neglecting the families and their children. Despite some difficulties it is concluded that the results indicate elements of the experience that can contribute to the construction within the municipalities of a more comprehensive action in order to guarantee the right of children and adolescents to live with a family and a community